Analysing students’ engagement in higher education through transmedia and Learning Management Systems: a text mining approach - Angelino, F. J.; Loureiro, S. M. C.; Bilro, R.G. (International Journal of Innovation and Learning, 2021)
This research aims to explore how students’ engagement can be promoted through transmedia using a set of activities within the Moodle Learning Management System for a syllabus topic about innovation, during a full semester. The analysis of case studies, the writing of essays, or the participation in an online forum were among the performed activities by a group of eightyone university students in their senior year. To perform the data analysis, we followed a mixedmethod approach between descriptive statistics, data mining analysis based on the open-source software Orange and a final questionnaire. The results achieved reveal that students’ engagement tends to increase by participating in the online forum and by performing some of the proposed tasks which required extensive information search from various media sources.